Jumping genomic gigantism. Issue 11 (November 2018) - Mueller, Rachel; Jockusch, Elizabeth
Genomic gigantism in amphibians originated through a single extraordinary jump overlying otherwise gradual change; genome size variation is related to both the external environment and life history in frogs, but may not be in salamanders.